DIFFICULTIES ENCOUNTERED BY PRESERVICE TEACHERS IN POLYTECHNIC UNIVERSITY OF THE PHILIPPINES - Palillo, Daizylyn Caan- (International Journal of Psychosocial Rehabilitation, 2020)
Practice teaching has been a platform for all pre-service teachers in Philippines for them to be trained and apply the theories they have learned inside the classroom. This has been found effective in preparing them for classroom management skills while learning both the content in a more in-depth way and the attitudes towards effective and efficient way of teaching. However, many of them encountered difficulties during this time. In this study, 127 preservice teachers were surveyed and found out that majority of them has difficulty in lesson planning, classroom management, instructional skills and assessment skills in terms of their gender but significant difference was not evident when grouped based on specialization. This implies that that females can easily adapt and implement acquired knowledge but males could perform better over time through experiential learning while specialization does not guarantee outstand